2011
DOI: 10.1111/j.1469-8986.2010.01078.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cold Face Test‐induced vagal inhibition and cortisol response to acute stress

Abstract: Low vagal function is related to several disorders. One possible underlying mechanism linking the vagus nerve and disorders is the HPA axis. Thirty-three healthy male subjects participated in a stress task, while heart rate (HR), respiratory sinus arrhythmia (RSA), salivary cortisol, and mood were assessed. Vagal function was determined using baseline, stress-induced inhibition, and Cold Face Test (CFT)-induced stimulation. The stress task induced a significant increase in cortisol and HR, a decrease in RSA, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 75 publications
9
28
0
1
Order By: Relevance
“…Several studies of emotional SR have reported that more adaptive emotion regulation strategies are associated with lower cortisol response to stress (e.g., Lam, Dickerson, Zoccola, & Zaldivar, 2009; Quirin, Kuhl, & Dusing, 2011). Likewise, RSA plays a role in inhibiting cortisol (see Thayer & Sternberg, 2006), producing negative relations between RSA or HRV and cortisol under stressful conditions, and between baseline cardiac indices and cortisol reactivity to stress (e.g., Bueno et al, 1989; Johnson, Hansen, Sollers, Murison, & Thayer, 2002; La Marca et al, 2011; Weber et al, 2010). Thus, these studies point to the role of top-down SR in the regulation of HPA axis activity in adults (for a review, see Dedovic, Duchesne, Andrews, Engert, & Pruessner, 2009).…”
Section: The Influence Of the Prenatal Environment On Children’s Selfmentioning
confidence: 99%
“…Several studies of emotional SR have reported that more adaptive emotion regulation strategies are associated with lower cortisol response to stress (e.g., Lam, Dickerson, Zoccola, & Zaldivar, 2009; Quirin, Kuhl, & Dusing, 2011). Likewise, RSA plays a role in inhibiting cortisol (see Thayer & Sternberg, 2006), producing negative relations between RSA or HRV and cortisol under stressful conditions, and between baseline cardiac indices and cortisol reactivity to stress (e.g., Bueno et al, 1989; Johnson, Hansen, Sollers, Murison, & Thayer, 2002; La Marca et al, 2011; Weber et al, 2010). Thus, these studies point to the role of top-down SR in the regulation of HPA axis activity in adults (for a review, see Dedovic, Duchesne, Andrews, Engert, & Pruessner, 2009).…”
Section: The Influence Of the Prenatal Environment On Children’s Selfmentioning
confidence: 99%
“…This procedure was chosen in order to prevent multiple testing (La Marca et al, 2011). In a first step, correlation analyses were conducted between these variables.…”
Section: Developmental Psychobiologymentioning
confidence: 99%
“…In a second step, hierarchical regression analyses were performed with those stress markers that were significantly associated with birth outcome. This procedure was chosen in order to prevent multiple testing (La Marca et al, 2011). Gestational length, birth weight, and birth size served separately as dependent variables.…”
Section: Developmental Psychobiologymentioning
confidence: 99%
“…During exposure to cold, the cortisol level in humans rises dramatically, except when they are exposed quickly (as in the cold face test), when there are reduced cortisol rises, perhaps due to vagal inhibition [35]. It is suspected that exposure to extreme cold temperature gives rise to a similar stress-like response with respect to cortisol levels in humans.…”
Section: Introductionmentioning
confidence: 99%